Synthesis and Characterisation of Schiff Base Complexes of Copper(II), Nickel(II), Vanadium(IV) and Uranium(VI)† - Jejurkar, C.R.; Parikh, Ketan (Asian Journal of Chemistry, 2010)
Two organic Schiff base ligands derived from phenylbutazone or oxyphenebutazone and o-aminophenol have been synthesised. Their eight metal complexes of Cu2+, Ni2+, VO2+ and UO2+2 have been prepared. The isolated ligands and metal complexes are characterised by elemental analysis, magnetic measurements, X-ray diffraction, reflectance and IR spectral studies. The Schiff base ligands and their metal complexes were tested for their antibacterial behaviour using E. Coli as a test organism. Uranium and vanadium complexes are found to be excellent antibacterial agents.